2013
DOI: 10.1002/ar.22661
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus‐mediated Interferon‐γ Gene Therapy Induced Human Pancreatic Carcinoma Capan‐2 Cell Apoptosis In Vitro and In Vivo

Abstract: Pancreatic cancer is one of the most lethal human malignancies with a very low 5-year survival rate, which highlights urgent needs for more effective therapeutic strategies. In this study, we examined the potential therapeutic effects of an adenovirus encoding human interferon gamma (Ad-IFNg) on pancreatic carcinoma cells Capan-2 in vitro and in vivo. The results indicated that Ad-IFNg could significantly inhibit tumor cell growth via inducing cell apoptosis. After infection, IFNg expressed durably and stably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Since IFN-γ can promote anti-tumorigenic effects through the activation of natural killer cell surveillance 1 2 3 4 , it is thought to be a prognostic factor for cancer therapy 5 6 7 8 . IFN-γ is also known as an anti-osteoclastogenic cytokine by its degradation of TRAF6, which results in the subsequent inhibition of RANKL signaling in osteoclasts 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since IFN-γ can promote anti-tumorigenic effects through the activation of natural killer cell surveillance 1 2 3 4 , it is thought to be a prognostic factor for cancer therapy 5 6 7 8 . IFN-γ is also known as an anti-osteoclastogenic cytokine by its degradation of TRAF6, which results in the subsequent inhibition of RANKL signaling in osteoclasts 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Interferon gamma (IFN-γ) is a cytokine that exerts an anti-tumor effect through the activation of natural killer cell surveillance 1 2 3 4 . Moreover, IFN-γ has been proposed as a prognostic factor in cancer therapy 5 6 7 8 . In addition to its anti-tumor functions, IFN-γ also exerts an anti-osteoclastogenic effect by inducing degradation of tumor necrosis factor receptor-associated factor 6 (TRAF6), resulting in the inhibition of receptor activator of nuclear factor (NF)-kappa B ligand (RANKL) signaling 9 .…”
mentioning
confidence: 99%
“…Interestingly, treating cancer with Ad-IFNα resulted in higher IFNα concentration in tumors than in systemic circulation ( Ohashi et al, 2005 ), and promoted regression of non-treated distant tumors as well, also inducing T-cells and natural killer cells recruitment to tumor site ( Hara et al, 2007 ). IFNβ in an oncolytic adenovirus improved treatment ( He et al, 2008 ; Park et al, 2010 ) and adenovirus expressing IFNγ showed low systemic toxicity ( Xie et al, 2013 ; Zhao et al, 2007 ).…”
Section: Adenovirus In Cancer Gene Therapymentioning
confidence: 99%
“…[8][9][10] Therefore the concept of delivering the necessary dose of treatment directly to the target tissue has been investigated with (a) gene therapy, (b) immunotherapy and (c) chemotherapy or combinations of the above methods. [11][12][13][14][15][16][17] The following methods for intratumoral treatment have been used: (a) brachytherapy, (b) photodynamic therapy, (c) thermal and non-thermal ablative therapies, (d) chemotherapy, and (e) gene therapy. 16,[18][19][20] Gene therapy has been used for lung cancer to sensitize cells to radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%